Conflict Communication Management for Couples in Preventing Divorce from an Islamic Perspective - Raychan Adhitya; Tatik Meiyuntariningsih; Sofia Gussevi (IJCRE - International Journal of Culture, Religion, and Education, 2025)
Divorce rates in DKI Jakarta continue to increase, particularly in South Jakarta, where cases reached 4,622. A similar trend is observed in Kemandoran, which recorded 497 divorce cases in 2023 based on data from the Central Statistics Agency (BPS). This year-to-year increase in divorce is largely caused by communication conflicts, persistent disputes, and continuous arguments. Each couple in Kemandoran exhibits different relationship patterns, and many couples are extremely busy, resulting in insufficient time for effective communication. Some couples are even required to live apart due to work demands. This study aims to identify the types of conflict and conflict communication management strategies used by couples to prevent divorce in Kemandoran, South Jakarta. The research employs a qualitative approach with a phenomenological design. Data collection techniques include in-depth interviews and documentation. Data analysis and interpretation follow three stages: (1) data condensation, (2) data display, and (3) conclusion drawing/verification, with source triangulation used to ensure the validity of findings. The results indicate that marital conflicts in Kemandoran, South Jakarta, include zero-sum and motive conflicts, personality-based and situational conflicts, as well as basic and non-basic conflicts. In managing conflict to prevent divorce, couples tend to apply an integrating or problem-solving communication style, allowing them to discuss issues openly, exchange perspectives, identify core problems, and collaboratively develop solutions. From an Islamic perspective, marriage is regarded as mitsaqan ghalizha (a strong covenant) that must be preserved through effective communication, mutual consultation (shūrā), and patience, as taught in the Qur’an and Sunnah to prevent divorce.